2016
DOI: 10.1093/jac/dkw242
|View full text |Cite
|
Sign up to set email alerts
|

Rise and fall of KPC-producingKlebsiella pneumoniaein New York City

Abstract: Over the past decade there has been a steady decline in KPC-producing K. pneumoniae in most New York City hospitals. The reason for the decline is probably multifactorial, involving a reduction in device (catheter) utilization and possibly an improvement in infection control practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…We found that 9.7% of K. pneumoniae bloodstream isolates were carbapenem-resistant overall, including 11.9% of isolates in NYC centers. Our findings are consistent with those of Abdallah and colleagues, who found that 13% of K. pneumoniae isolates from multiple NYC medical centers during a similar time period possessed bla KPC (17). In contrast, recent national surveillance studies reported carbapenem resistance in only 3 to 6% of K. pneumoniae (18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
“…We found that 9.7% of K. pneumoniae bloodstream isolates were carbapenem-resistant overall, including 11.9% of isolates in NYC centers. Our findings are consistent with those of Abdallah and colleagues, who found that 13% of K. pneumoniae isolates from multiple NYC medical centers during a similar time period possessed bla KPC (17). In contrast, recent national surveillance studies reported carbapenem resistance in only 3 to 6% of K. pneumoniae (18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
“…This effect has similarities with other enteropathogenetic syndromes such as Clostridium difficile colitis and candidaemia, at least by the means of exogenous colonization [103,104]. In a multicentre US study, KPC-KP clearance was attributed to a reduction in the use of urinary catheters, a factor that should be considered in the implementation of a bundle procedure [105].…”
Section: Can Kpc-kp Infections Be Prevented? How?mentioning
confidence: 94%
“…14 In a New York-based multicenter survey, the prevalence of bla KPC within K. pneumoniae isolates peaked at 36% in 2006. 23 Of great interest, a notable decline has since been recorded to 25% in 2009 and 13% in 2013-2014. 23 Spread to the Great Lakes region of the United States has been described.…”
Section: Where Are Cpe Found?mentioning
confidence: 99%
“…23 Of great interest, a notable decline has since been recorded to 25% in 2009 and 13% in 2013-2014. 23 Spread to the Great Lakes region of the United States has been described. The Consortium on resistance against carbapenems in Klebsiella and other Enterobacteriaceae (CRACKLE) is a prospective, multicenter, observational study of hospitals in Ohio, Pennsylvania and Michigan.…”
Section: Where Are Cpe Found?mentioning
confidence: 99%